Information sources influencing students' choice of private colleges in Malaysia: an exploratory perspective / Nooraini Sheriff - Sheriff, Nooraini (ACRULeT, Faculty of Education & UiTM Press, 2007)
This study examined students' perceptions of the influence of information sources that led to their choice of private college. Data were solicited from 808 newly enrolled students in 72 multi-discipline private colleges in Malaysia through random sampling. A two part questionnaire consisting of background data and students' perceptions of the influence of information sources for the selection of private colleges was distributed through the 'drop-off' method and mail survey. Likert-like scales with values ranging from 0 (Not applicable), 1 (low) to 7 (high) were used to obtain responses. One hundred and seventy (21%) students reported their personal experience, an internal source, as having moderate influence on their choice of private college. Within the category of personal sources such as friends, a type of external source, 236 (29.2%) perceived them as a moderate influence. The National Accreditation Board and the Ministry of Education, an external independent source, were perceived by 176 (21.8%) students to have a strong influence on their decision making process. As for other external information sources, 206 (25.5%) students perceived course counselors, a commercial source, to have moderate influence, and 191 (23.6%) students perceived personal inspection, an experiential source, to have a strong influence on their decision to choose a private college. The findings imply that there are varying degrees of influence among the different sources that affect students' choice of private college. This highlights the need for private colleges to review their promotional tools, media, message, timing and frequency to disseminate the necessary information in the most effective manner to achieve the targeted enrolment.